OVARIAN RESPONSE OF DAIRY COWS TO PROGESTERONE COMBINED ON - Toleng, A.L.; Yusuf, M.; Hasbi, H.; Putri, A.R.M. (Diponegoro University, 2013)
The objective of this study was to evaluate the response of ovaries in estrus synchronizationprotocol using GnRH-PGF2α based protocol combined progestin in a herd with tie-stall housing system.A total of 20 Holstein Friesian cows at different stages of estrus cycle in a dairy herd were enrolled inthe present study. The cows were randomly allocated into two treatment groups; with and without CIDR(Controlled internal drug release) insertion. All cows received 100 μg of GnRH I.M. at the beginning ofthe treatment (d 0) without regard to the stages of the estrus cycle followed by 25 mg PGF2α IM 7dayslater. Cows in CIDR group were inserted CIDR into the vagina at the time of GnRH administration andwere removed on the day of PGF2α administration. estrus signs were checked twice daily starting onday-2 after initiation of the protocol, except cows in CIDR group the estrus signs were checked startingon day-8 of the protocol. The animals showing estrus signs were noted. Blood samples were collectedfrom all animals on the days of GnRH and PGF2α treatments and on day-10 after initiation of protocolfor progesterone concentration. The results of this study showed that 30% animals in cows withoutCIDR insertion showed estrus signs prior to PGF2α injection. Involving CIDR to synchronized estruswith GnRH-PGF2α based protocol avoided the occurrence of premature estrus and maintained highprogesterone concentration on the day of PGF2α administration. It is concluded that ovarian responseafter involving CIDR in the protocol for estrus synchronization especially using combination of GnRHand PGF2α were much effective to synchronize the initiation of estrus in dairy cows. Likewise, the useof progesterone avoided premature estrus.